PENGARUH HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS PENGGUNA SMARTPHONE SAMSUNG (Studi Pada Mahasiswa Magister Manajemen UNKRIS) - Ella Siti Chaeriah (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
Loyalty is the willingness of consumer to continue to subscribe at a company in the long run by buying and using goods and services, is repeate dlyreworked and better yet exclusively and voluntarily recommend the company product to others. This study devoted tol analysis influence of price empiricly variable, brand image, product quality to loyality and to known variable that gae. Most dominant influence, which is price,brand image and produk quality to loyalty in jakarta smartphone mobile in jakarta. Collected data method used questioner. Population was student Magister Manajemen UNKRIS. Want to used Samsung smartphone. Sample was 30 respondent with purposive sampling technique. Analysis result with statistic SPSS with double regression linier, Y = 2,453 + 0,250X1 + 0,205X2 + 0,397X3 double regression linier show there are positive influence and significant from price variable, brand image and product quality to loyalty customer smartphone.